Pandemics, Science and Policy - Abeysinghe, S. author. aut Link
V, 243 p.
Keywords: Pandemics, Science and Policy analyses the World Health Organisation's (WHO) management of the 2009 H1N1 Pandemic. Abeysinghe illustrates the ways in which the WHO's account was vulnerable to contestation, and ultimately how uncertain risks can affect policy and action on the global level.